Doctors’ knowledge and attitudes on pain assessment and management in Queen Elizabeth Hospital, Kota Kinabalu, Sabah - T. Kumaravadivel Dharmalingam; Rajesh Kumar Muniandy (2020)
Introduction: Doctors play an important role to assess and manage pain. Failing to do so properly, pain will affect the quality of life and increase the length of hospital stay for patients. In Queen Elizabeth Hospital (QEH), Kota Kinabalu, Sabah, pain assessment and management programs have been conducted on a regular basis. However, there has been no studies to assess the effectiveness of these programs. Methodology: This is a cross-sectional study to assess the knowledge and attitude on pain assessment and management among medical officers at QEH. A universal sampling technique was used, to represent medical officers from major clinical departments. The Knowledge and Attitudes Survey Regarding Pain (KASRP) questionnaire was used for this study. Results: A total of 278 questionnaires were distributed to medical officers. The study sample consisted of 125 females (44.9%), and 153 males (55.1%). The age group of the participants ranged from 25 to 41 years old. A 116 respondents scored less than 60% on the knowledge of pain (41.7%). These findings show there was a deficit in their knowledge and attitude about pain. There was also a difference of scores between genders, where the male doctors performed better than the female doctors. There was a difference between scores among doctors from different departments. The highest mean score was from the department of Anaesthesia (80.2%). There was also a difference regarding pain knowledge based on the years of working as a doctor, where the highest passing rate was from doctors working for more than five years. Conclusion: This study demonstrated that there is a lack of knowledge and attitude on pain assessment and management among QEH medical officers who responded to this study. This will support the plan on a more aggressive and continuous education programme to improve pain assessment and management among doctors in QEH.